ALGAE BIOMASS AS A SUSTAINABLE ALTERNATIVE TO INORGANIC FERTILIZERS: A STUDY ON ITS FATE IN AGRICULTURAL SOIL AND EFFECT ON SOIL MICROBIAL DIVERSITY - Alobwede, E; Leake , J.R (Academic Journal of Psychology and Education (AJPE), 2023)
Inorganic fertilizers contribute to the eutrophication of water bodies, causing algal blooms that harm the environment. Using microalgal biomass as a fertilizer may replenish soil nutrients and reduce the need for inorganic fertilizers. This study explored the potential of microalgal biomass as a circular economy fertilization solution in agriculture. A 15N tracer study was conducted to investigate the fate of nitrogen derived from a common unicellular green alga, Chlorella vulgaris, into soil and wheat nitrogen pools under greenhouse conditions. The results show that the soil retained a higher amount of algal nitrogen (10.3%) compared to the wheat shoot (0.7%) after 30 days. The study also assessed the impact on soil bacterial communities through 16S rDNA sequencing, which showed that adding microalgal biomass to agricultural soils improved nitrogen fertilization and soil health by increasing soil microbial diversity. This may be a cost-effective nutrient management strategy on agricultural farms and mitigate the negative environmental impact of inorganic fertilizers.